Local variations in the timing of RSV epidemics. Issue 1 (December 2016) - Noveroske, Douglas; Warren, Joshua; Pitzer, Virginia; Weinberger, Daniel
Abstract Background Respiratory syncytial virus (RSV) is a primary cause of hospitalizations in children worldwide. The timing of seasonal RSV epidemics needs to be known in order to administer prophylaxis to high-risk infants at the appropriate time. Methods We used data from the Connecticut State Inpatient Database to identify RSV hospitalizations based on ICD-9 diagnostic codes. Harmonic regression analyses were used to evaluate RSV epidemic timing at the county level and ZIP code levels. Linear regression was used to investigate associations between the socioeconomic status of a locality and RSV epidemic timing. Results 9, 740 hospitalizations coded as RSV occurred among children less than 2 years old between July 1, 1997 and June 30, 2013. The earliest ZIP code had a seasonal RSV epidemic that peaked, on average, 4.64 weeks earlier than the latest ZIP code. Earlier epidemic timing was significantly associated with demographic characteristics (higher population density and larger fraction of the population that was black). Conclusions Seasonal RSV epidemics in Connecticut occurred earlier in areas that were more urban (higher population density and larger fraction of the population that was). These findings could be used to better time the administration of prophylaxis to high-risk infants.